2021
DOI: 10.1108/ijqrm-02-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of maintenance strategies and data application in asset performance management for both developed and developing countries

Abstract: PurposeThe present study empirically compares maintenance practices under asset performance management (APM), employed by firms in developed and developing countries (Belgium and Kenya, respectively).Design/methodology/approachEmpirical observations and theoretical interpretations on maintenance practices under APM are delineated. A comparative cross-sectional survey study is conducted through an online questionnaire with 151 respondents (101 Kenya, 50 Belgium). Descriptive statistics and inferential statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Moreover, it has been observed that the data collected for performance measurement are not adequately used in decision support (Muchiri et al, 2010). On the one hand, the large number of data collected becomes a problem, as they require more sophisticated methods and algorithms to elicit useful information (Villarejo et al, 2017;Wakiru et al, 2022). On the other hand, the reviewed indicator selection methods take a one-way path from identifying to screening MPIs.…”
Section: Choice Of Performance Indicatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it has been observed that the data collected for performance measurement are not adequately used in decision support (Muchiri et al, 2010). On the one hand, the large number of data collected becomes a problem, as they require more sophisticated methods and algorithms to elicit useful information (Villarejo et al, 2017;Wakiru et al, 2022). On the other hand, the reviewed indicator selection methods take a one-way path from identifying to screening MPIs.…”
Section: Choice Of Performance Indicatorsmentioning
confidence: 99%
“…On the one hand, the large number of data collected becomes a problem, as they require more sophisticated methods and algorithms to elicit useful information (Villarejo et al. , 2017; Wakiru et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, effective maintenance planning is necessary to ensure that the equipment keeps operating securely, avoiding economic, social and environmental losses. Besides, a timely and high-quality supply of spare parts for equipment can reduce the failures and decrease the periods of shutdown (Wakiru et al, 2022), thus, the maintenance suppliers play a crucial role regarding the accessibility of spare parts to guarantee the overall quality of the manufactured products. So, it is vital to have a firm plan for dealing with the suppliers (Antosz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%